Knowledge Diffusion, Endogenous Growth, and the Costs of Global Climate Policy - Lucas Bretschger; Filippo Lechthaler; Sebastian Rausch; Lin Zhang (ETH Zurich, CER-ETH - Center of Economic Research, 2015)
This paper examines the effects of knowledge diffusion on growth and costs of climate policy. We develop a general equilibrium model with endogenous growth which represents knowledge diffusion between sectors and regions. Knowledge diffusion depends on accessibility and absorptive capacity which we estimate econometrically using patent and citation data. Knowledge diffusion leads to a “greening” of economies boosting productivity of “clean” carbon-extensive sectors. Knowledge diffusion lowers the costs of global climate policy by about 90% for emerging countries (China) and 20% for developed regions (Europe and USA), depending on the substitutability between different knowledge types.
Keywords: O33; O44; Q55; C68; 330; Technological Change: Choices and Consequences; Environment and Growth; Technological Innovation; Computable General Equilibrium Models; Wissenstransfer; Wirtschaftswachstum; Internationale Klimapolitik; Soziale Kosten; Allgemeines Gleichgewicht; Endogenes Wachstumsmodell; Europa; USA; China